Selected solutions for rehabilitation of wooden structures: some Portuguese case studies - Feio, A. (2013)
Timber is one of the most used materials in the roofs and floors of monumental constructions in Portugal. The geometry is defined by elements that occupy a limited and well defined part of the tri-dimensional space, with a clear evidence of the hierarchy of the components. Timber elements are often visible, which allows easier conservation, identification of the wood species, characterization of details and evaluation of deterioration. Complex timber structures, such as those belonging to the roofs of large monuments, are often not easy to understand in a expedite way. As the coverings of monuments as cathedrals, public buildings, mansions or villas show very complicate features, not easy to be understood during the first inspection. This is not only due to the fact that the system is very elaborate and to the large number of members but also due to continuous changes and repair past works, mostly with additional stiffening or propping. The typical result of the history of the construction is the increase in the number and the heterogeneity of the members, together with a multiplicity of connections and diversity of supports. This means that the original must be distinguished from the additions and the replacements. This complexity makes the field of conservation of historical timber structures not only a challenge but a field much in need of modern research. The objective of this paper is to present some of the Portuguese experience in this field, showing how the rehabilitation solutions can be supported by the inspection techniques and by an extensive knowledge about the constituent material from which the structure was made, both from the mechanical point of view and from the physical point of view. A number of case studies will be presented to illustrate common conservation problems, and design problems as well as the possibilities and limitations of several solutions and to discuss the suitability of several intervention methods.